The Dual Nature of Foreign Currency Debt and Its Impact on Firm Performance: Evidence from French Non-Financial Firms - Mefteh-Wali, Salma; Rigobert, Marie-Josèphe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
We investigate the impact of foreign currency debt on firm performance for a sample of non-financial French firms studied over the period 2002 to 2012. As foreign currency debt is both a financing and hedging instrument against foreign exchange risk, we examine whether its impact results from an optimal hedging policy or a capital structure policy. We find that foreign currency debt and domestic debt have the same positive effect before the crisis and negative impact after. The capital structure theory or the hedging theory can explain this result. During the crisis period, only corporate hedging theory explains the impact of foreign debt.